Unconscious pop-out: attentional capture by unseen feature singletons only when top-down attention is available - Hsieh, Po-Jang (2011)
Visual “pop-out” occurs when a unique visual target (e.g. a feature singleton) is present among a set of homogeneous distractors. However, the role of visual awareness in this process remains unclear. Here we show that, even though subjects were not aware of a suppressed pop-out display, their subsequent performance on an orientation discrimination task was significantly better at the pop-out location than at a control location. These results indicate that visual awareness of a feature singleton is not necessary for it to attract attention. Furthermore, our results show that the subliminal pop-out effect disappeared when subjects diverted their attention toward an RSVP task while viewing the same subliminal pop-out display, suggesting that the availability of top-down attention is necessary for the subliminal pop-out effect, and that the cognitive processes underlying attention and awareness are somewhat independent.